A Review Paper on Garbage Level Monitoring System for Smart Cities - D.M.Yadav , Neha Ganvir, Sujay Deshpande (Mathematical Statistician and Engineering Applications, 2022)
As the population is increasing day by day, the environment should be clean and hygienic. In many of the cities the overflowing garbage bins are creating an unhygienic environment. This further leads to arise of different types of diseases. To cope up with the situation, Shree Narendra Modi, PM of India has presented a unique example of a way to achieve cleanliness by launching a campaign popularly known as SWACCHHA BHARAT ABHIYAN (Clean India Mission) in which every individual irrespective posts and authority, has to maintain clean surrounding. In this contemporary busy world, it is almost impossible to maintain the clean and hygienic environment. To overcome these situations, we need to implement a smart garbage level monitoring system, which will alert the municipal corporation or higher authorities about the current level of garbage in different zones of cities. As level reaches its threshold level the alert is send to corporation. As the notification is received by the municipal corporation, the rag picking truck will reach to that dustbin and will empty the bin. Hence the bins are emptied before the garbage starts overflowing.